The Effects of functional treatment of V metatarsal bone fracture in athletes – an evaluation of cases - Kacprzak, Bartłomiej; Krzymińska, Klaudia; Siuba, Natalia; Miler, Adrian; Hagner-Derengowska, Magdalena; Kitschke, Ewa; Zukow, Walery (Journal of Education, Health and Sport, 2024)
This study presents the rehabilitation process for the management of six cases of fractures of the fifth metatarsal bone in players of various sports playing at high levels of competition in Poland. The course of treatment was based on an intensive rehabilitation protocol with the need for orthopaedic shoe inserts, with full weight bearing on the limb and under close supervision of a physiotherapist. The effectiveness of rehabilitation was assessed by physical examination, X-ray examination and the numerical pain rating scale - NRS. This study focuses on the rehabilitation process for managing fractures of the fifth metatarsal bone in high-level athletes in Poland. The treatment involved an intensive rehabilitation protocol with orthopaedic shoe inserts, full weight bearing, and physiotherapist supervision. The effectiveness of rehabilitation was evaluated through physical exams, X-rays, and the numerical pain rating scale. Introduction Fractures of the fifth metatarsal bone are common in athletes aged 10-29, especially in football, basketball, and dance. Complications include delayed bone fusion and repeat fractures, emphasizing the importance of quick return to fitness. The involvement of physiotherapists and patient positivity is crucial. The debate among clinicians stems from classification variations and interpretations of ’Jones fractures’. Diagnostic and Classification Methods The Lawrence and Bottle classification distinguishes three types of metatarsal fractures: avulsion, Jones, and fatigue fractures. The study presents six cases of conservative treatment for these fractures, showing positive outcomes in returning athletes to competition. Rehabilitation Procedure Patients underwent functional treatment with orthopaedic insoles, immediate weight-bearing, and various therapies like Orthokine®, Exogen, hyperbaric chamber sessions, ESWT, and EPTA. Post-workout treatments included Game Ready®, flossing, manual therapy, dry needling, and lymphatic drainage. Patients also engaged in self-managed rehabilitation exercises. Treatment Results Radiographic examinations showed progressive healing in all cases, with reduced pain and no edema after two weeks. Patients returned to sports within three weeks, with no complaints after 13 months. The study highlights the success of functional treatment in achieving full recovery without complications. Conclusion The study challenges the need for surgical intervention and immobilization in treating fifth metatarsal fractures. Functional treatment led to excellent outcomes and quick return to sports. Literature review supports early mobilization and functional therapy for optimal results. Further research is needed to establish a standard treatment protocol based on evidence-based medicine.